Characterization of foam glass produced from waste CRT glass and aluminium dross. (April 2020) - Sassi, M; Ibrahim, J F M; Simon, A
Abstract: Increasing the energy efficiency of buildings has become very pertinent currently. This will be implemented by employing eco-friendly materials such as foam glass. Glass foaming is a process that depends strongly on the foaming mechanism and the initial composition of the mixture. This study deals with the investigation of foam glass properties consisting of recycled bottle glass material, CRT glass and aluminium dross. Experiments were carried out to investigate the thermal behaviour, optimal foaming temperature, density, water absorption, thermal conductivity and compressive strength of the foams. Microstructure and cell size distribution was analyzed as well. Effect of the CRT glass and the aluminium dross on the properties of the foams was evaluated in this paper. Adding aluminium dross decreased the foaming temperature, increased the foaming height and enhanced the compressive strength of the foam glass.